GEOLOGI DAERAH MINAWEROT DAN SEKITARNYA, KECAMATAN KAUDITAN, KABUPATEN MINAHASA UTARA, SULAWESI UTARA - Luntungan, Paskah Richo; Budiharso, Agus Santoso; Rachmadhan, H.D. (LPPM Universitas PRISMA, 2024)
The research location is administratively in North Sulawesi Province, precisely in Kaima Village, Lembean Village, Kaasar Village and Treman Village, Kauditan District, North Minahasa Regency. It is located at the coordinates of 1°16'0